2007
DOI: 10.1136/hrt.2007.118638
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary embolism causes endomyocarditis in the human heart

Abstract: In patients with PE, endomyocarditis and intracavitary thrombi in the left and right ventricle were found. These abnormalities may be an additional new explanation for the observed cardiac enzyme release and functional abnormalities of the heart in these patients and may contribute to the morbidity and mortality of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 30 publications
(23 reference statements)
3
39
2
5
Order By: Relevance
“…However, in patients suffering from acute pulmonary embolism, comparable observations of selective RV inflammation were reported in a postmortem study, 18 and similar findings were observed in experimentally induced acute pulmonary embolism. 28 The mechanistic importance of RV inflammation was demonstrated because suppression of the inflammatory response after acute pulmonary embolism limited RV damage and prevented right heart failure.…”
Section: Worsened Survival After Training Associated With Enhanced Rvsupporting
confidence: 63%
“…However, in patients suffering from acute pulmonary embolism, comparable observations of selective RV inflammation were reported in a postmortem study, 18 and similar findings were observed in experimentally induced acute pulmonary embolism. 28 The mechanistic importance of RV inflammation was demonstrated because suppression of the inflammatory response after acute pulmonary embolism limited RV damage and prevented right heart failure.…”
Section: Worsened Survival After Training Associated With Enhanced Rvsupporting
confidence: 63%
“…The relationship between elevated WBC count and left ventricular dysfunction in patients with acute coronary syndrome and the various potential mechanisms of myocardial injury mediated by leukocytes have been described in detail [3]. There is growing evidence from animal and autopsy studies that acute PE with at least moderately severe pulmonary hypertension results in right ventricular myocyte lysis and infiltration by neutrophils, macrophages, and lymphocytes in humans and rats [12][13][14][15]17] and that this inflammation independently amplifies injury [25]. Therefore, an elevated WBC count may indicate PE-related right heart dysfunction, a known factor for adverse prognosis in patients with PE [11].…”
Section: Discussionmentioning
confidence: 99%
“…Early death after PE is strongly associated with right ventricular dysfunction [11]. Animal and autopsy studies demonstrated that neutrophils are not only involved in the development of venous thrombosis but that an influx of neutrophils and other WBCs may contribute to right ventricular dysfunction following PE [12][13][14][15][16][17]. Moreover, the WBC count also correlates with levels of fibrinogen, factor VII, and factor VIII and thus, may be a marker for hypercoagulability [18].…”
Section: Introductionmentioning
confidence: 99%
“…Обнаружение массивных инфильтратов в миокарде ПЖ у больных, умерших от острой ТЭЛА в течение 48 ч, можно объяснить высо ким уровнем адреналина, который высвобождается при развитии миокардита, вызванного ТЭЛА [74]. Воспалительный ответ также может быть обусловлен и вторичной гемодинамической нестабильностью, которая иногда развивается в течение 24-48 ч после острой ТЭЛА, хотя в некоторых случаях альтерна тивным объяснением могут служить ранние рециди вы ТЭЛА [75].…”
Section: течениеunclassified